Grade III or Grade IV Hypertensive Retinopathy with Severely Elevated Blood Pressure - Henderson, Amanda D. (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2012)
INTRODUCTION: Hypertensive retinopathy describes a spectrum of retinal changes in patients with elevated blood pressure (BP). It is unknown why some patients are more likely to develop acute ocular end-organ damage than others with similar BP. We examined risk factors for grade III/IV hypertensive retinopathy among patients with hypertensive urgency in the emergency department (ED) and compared healthcare utilization and mortality between patients with and without grade III/IV hypertensive retinopathy. METHODS: A preplanned subanalysis of patients who presented to a university hospital ED with diastolic BP ≥ 120 mmHg and who enrolled in the Fundus Photography versus Ophthalmoscopy Trial Outcomes in the ED study was performed. Bilateral nonmydriatic ocular fundus photographs, vital signs, and demographics were obtained at presentation. Past medical history, laboratory values, healthcare utilization, and mortality were ascertained from medical record review at least 8 months after initial ED visit. RESULTS: Twenty-one patients with diastolic BP ≥ 120 mmHg, 7 of whom (33%) had grade III/IV hypertensive retinopathy, were included. Patients with retinopathy were significantly younger than those without (median 33 vs 50 years, P= 0.02). Mean arterial pressure (165 vs 163 mmHg) was essentially equal in the 2 groups. Patients with retinopathy had substantially increased but nonsignificant rates of ED revisit (57% vs 29%, P = 0.35) and hospital admission after ED discharge (43% vs 14%, P = 0.28). One of the patients with retinopathy died, but none without. CONCLUSION: Younger patients may be at higher risk for grade III/IV hypertensive retinopathy among patients with hypertensive urgency. Chronic compensatory mechanisms may have not yet developed in these younger patients. Alternatively, older patients with retinopathy may be underrepresented secondary to increased mortality among these patients at a younger age (survivorship bias). Further research is needed to validate these preliminary findings.